Melestarikan keanekaragaman hayati melalui proses pembelajaran di kelas dan penugasan - Rachmawati, Rizqi Nur; Hermawan, Hermawan; Haerani, Yeni; Wijaya, Devi Intan; Ningsih, Siti Nurastia (Jurnal Kajian Pendidikan IPA, 2024)
Indonesia is a very large country consisting of large islands which certainly have abundant diversity. Indonesia is known as mega-biodiversity which has a very large number of flora and fauna known to be second in the world after Brazil. Biodiversity also has many benefits for humans, especially in wood plants, including as materials in making house buildings, firewood or other human needs, these plants should also be preserved and preserved for the survival of humans when they need it, besides that, this study aims to foster attitudes in preserving and maintaining biodiversity in students as the next generation of educators through the learning process outside the classroom or in the surrounding environment by giving challenging tasks to students. The subject of this research is the biology study program students in the biodiversity course with a total of 30 students. The type of research used is PTK (class action research) which is carried out with 2 cycles, cycle I and cycle II, with this research approach is a qualitative descriptive approach. Data analysis was carried out by triangulating data and using percentages and observations on student attitudes using a Likert scale, observation sheets and field notes as well as other documentation such as photos and supporting images in the research. The results of the research are that there is an increase in student attitudes at the implementation of cycle I, at the end of cycle I and at the end of cycle II, besides that there is an increase in student understanding after cycle II is implemented. It is hoped that teachers or lecturers in teaching, can apply the learning process outside the classroom and provide challenging tasks for students or students so that the teaching and learning process inside and outside the classroom feels more fun and challenged. Keywords: Biodiversity, Learning Process, Assignment